Molossops temminckii (Chiroptera: Molossidae). (12th August 2019) - Gamboa Alurralde, Santiago; Díaz, M Mónica
Abstract: The dwarf dog-faced bat, Molossops temminckii (Burmeister, 1854), is a small molossid bat that occurs from Colombia, Venezuela, and Guyana, southwestward through Ecuador, Peru, Bolivia, Paraguay, Brazil, Uruguay, and Argentina. It is one of two species in the genus Molossops and usually roosts in man-made structures, rock crevices, and hollow trees. The species is insectivorous, inhabits a variety of habitats, and is typically found in low altitude zones. Diagnostic characters include triangular ears separated by a wide space, one lower incisor in each ramus, and a last upper molar with three clearly marked commissures. Molossops temminckii is listed as "Least Concern" by the International Union for Conservation of Nature and Natural Resources.